Lower chest compression fraction associated with ROSC in OHCA patients with longer downtimes - Talikowska, Milena; Tohira, Hideo; Inoue, Madoka; Bailey, P.; Brink, D.; Finn, Judith (Elsevier, 2017)
© 2017 Elsevier B.V. Aim To investigate the relationship between chest compression fraction (CCF) and survival outcomes in OHCA, including whether the relationship varied based upon downtime from onset of arrest to provision of cardiopulmonary resuscitation (CPR) by emergency medical services (EMS). Methods Data from resuscitations performed by St John Ambulance Western Australia (SJA-WA) paramedics between July 2014 and June 2016 was captured using the Q-CPR feedback device. Logistic regression analysis was used to study the relationship between CCF and return of spontaneous circulation (ROSC). Various lengths of Q-CPR data were used ranging from the first 3 min to all available episode data. Cases were subsequently divided into groups based upon downtime; ≤15 min, > 15 min and unknown. Univariate and multivariable logistic regression analyses were performed in each group. Results There were 341 cases eligible for inclusion. CCF >  80% was significantly associated with decreased odds of ROSC compared to CCF ≤ 80% (aOR: 0.49, 95%CI: 0.28–0.87). This relationship remained significant whether the first 3 min of data was used, the first 5 min or all available episode data. Among the group with a downtime > 15 min, CCF was significantly lower for those who achieved ROSC compared to those who did not (mean (SD): 73.01 (12.99)% vs. 83.05 (9.38)% p = 0.002). The adjusted odds ratio for achieving ROSC in this group was significantly less with CCF  >  80% compared to CCF ≤ 80% (aOR: 0.06, 95%CI: 0.01–0.38). Conclusion We demonstrated an inverse relationship between CCF and ROSC that varied depending upon the time from arrest to provision of EMS-CPR.